Disease Specific to Chronic Lymphedema and Class III Obesity - Karen G. Figenshau; Matthew B. Lindquist (Case Reports in Medicine)
Elephantiasis nostras verrucosa (ENV) is a unique, chronic condition found in patients with obesity and chronic secondary lymphedema. It develops due to chronic inflammation and recurrent infection, most commonly on gravity-dependent sites. Progressive tissue enlargement, deformity, and disability necessitate intervention. First, clinicians should explore the etiology of patients’ secondary lymphedema, as this is paramount in determining treatment for ENV. The fundamental goal is alleviating lymphatic obstruction. Our literature review of available cases of ENV elucidates Class III obesity as a factor common to all available cases of ENV. As such, weight loss is a key component of treatment. Medical management and weight loss are most effective when combined with physiologic interventions such as compression garments and decongestive physiotherapy. If surgical intervention is required, one of the mainstays of patient management is a reductive approach, aimed at removing excess adipose and fibrotic tissue to improve lymphatic patency and flow. Optimal postoperative outcomes are achieved when patients also undergo physiologic procedures to bypass obstructions and connect functioning lymphatic vessels.